ETNOGRAFI PEMBELAJARAN LITERASI SAINS MATERI BUNYI MELALUI EDUWISATA PEMBUATAN GAMELAN DI DESA BANJAR, KERTEK, WONOSOBO - Hadad Sakan, Diana; Ahmad Khoiri; Desty Putri Hanifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The lack of integration between cultural literacy and scientific literacy in schools, especially in gamelan making, makes students not understand the relationship between the concepts of vibration and wave theory with cultural heritage such as gamelan. Educational tourism activities are activities that can be used to introduce culture as well as the principles of vibration, waves, frequency, and amplitude in physics learning based on local contexts. The implementation of the research used a qualitative ethnographic approach with an interpretive paradigm approach that allows researchers to be actively involved in observing, learning, and interacting directly with gamelan craftsmen. Data collection used participatory observation, in-depth interviews, and using field documentation. The object of the study was the Gamelan Making Center in Banjarsari Hamlet. The research subjects were gamelan craftsmen, tourism awareness groups who were members of the educational tourism, and participants of the Banjar Village educational tourism. The data analysis technique used ethnography by Spradley which went through 12 stages. The results of the study revealed that gamelan craftsmen utilize their hearing that has been accustomed to the sound of the gamelan to tune the notes, without realizing that this is related to the concept of physics. Gamelan craftsmen still make gamelan in a traditional way, and it is very interesting when educational tourism activities raise this issue.